2015
DOI: 10.1007/s11046-015-9894-1
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Amphotericin B-Tolerant Persister Formation is Closely Related to Surface Adhesion

Abstract: Candida albicans persisters have so far been observed only in biofilm environment; the biofilm element(s) that trigger(s) persister formation are still unknown. In this study, we tried to further elucidate the possible relationship between C. albicans persisters and the early phases of biofilm formation, especially the surface adhesion phase. Three C. albicans strains were surveyed for the formation of persisters. We tested C. albicans persister formation dynamically at different time points during the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…We encountered a technical problem at the biofilm recovery step, usually performed by scraping the cells in 1x PBS and vortexing prior to plating (8, 13, 15, 22). In our hands, the cells could not be properly resuspended and plated, as clumps of the biofilms would usually remain stranded inside the tips.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We encountered a technical problem at the biofilm recovery step, usually performed by scraping the cells in 1x PBS and vortexing prior to plating (8, 13, 15, 22). In our hands, the cells could not be properly resuspended and plated, as clumps of the biofilms would usually remain stranded inside the tips.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the experiments for this study were performed using in vitro biofilm model of C. albicans , developed in polystyrene 96-well plates. Following this work and relying on the protocol for persister cells isolation described therein (8), persister cells in C. albicans biofilms were described by a few other groups (1315). However, later work by the Douglas group showed that not all Candida species and strains were able to form persister cells in laboratory-grown biofilms (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the experiments for this study were performed using an in vitro biofilm model of C. albicans developed in polystyrene 96-well plates. Following this work and relying on the protocol for persister cells isolation described therein (8), persister cells in C. albicans biofilms were described by a few other groups (14)(15)(16). However, later work by Al-Dhaheri and Douglas showed that not all Candida species and strains were able to form persister cells in laboratory-grown biofilms (17).…”
mentioning
confidence: 97%
“…This was in particular the case for C. albicans strain SC5314 (18), the parental strain of almost all C. albicans strains used for functional genomics and molecular genetics studies. Unlike in the previously mentioned papers (8,(14)(15)(16), the protocol Al-Dhaheri and Douglas (17) used for persister isolation involved growing biofilms on silicone discs, followed by their immersion into an antifungal solution. As the topic of C. albicans persister cells remains controversial, the main objective of this work was to reevaluate their occurrence in in vitro-grown C. albicans biofilms.…”
mentioning
confidence: 99%